ANALYSIS OF WORD AND SENTENCE STRESS IN ENGLISH LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Stress is one of the most important speech tools used by English speakers to communicate meaning. English speakers use stress to highlight information they think is important. In addition, every English word with more than one syllable or word part has a defined stress pattern. This article,which attempts to deal with both the word stress and the sentence stress in a normative way, is based on the qualitative explorative research design. It involves the fundamental rules of word and sentence stress as variables.